(untitled) (Linguostylistic Studies, 2020)
The article analyzes the linguistic means of creating the image of wind in the poems by B-I.Antonych and argues that the poet’s vision of this image is a unique combination of the traditional and modern. The poet’s worldview is holistic by nature, and accordingly, all the elements in his works are closely interrelated and, at the same time, contradicting each other. The vivid and metaphorical language of his poetry reflects the philosophical, literary, artistic, and linguistic trends of the first decades of the XX century. The core lexeme wind in the poet’s linguistic creativity acquires new multifaceted figurative meanings and emotionally expressive shifts. The image of wind is correlated with the established symbolic and metaphorical associations: wind – spring – youth, wind – the energy of movement – unreserve, wind – space – freedom. The image of wind is also characterized by ambivalence. It is a symbol of thirst for life and young ardor, and, simultaneously, a symbol of obstacles and confrontation. The use of metaphorical transferences, based on various associations, allowed the poet to transform the phenomenon of nature into a lyrical hero, full of energy of movement. Most often, the author uses the metaphor of music – the wind, which is motivated by his perception of nature as continuous music of existence. In general, movement and sound are dominant in the structure of this image. With the help of metaphors, the author created a sensory image of wind, having involved acoustic, visual, tactile, and olfactory image-perceptions. The study has revealed that the metaphorical model of man → wind extends to the following areas of associations: man as a social being, age differentiation, appearance and character traits, and the actualization of a gender. The verbalized image of wind comprises the associations typical of the language of folklore, and, alongside, it is the embodiment of the poet’s individual vision of the world. It is a particular unity in which the tradition and innovation interact, which directly affects the content of symbols and metaphorsю